Aspects ecological of benthic communities in a fluvial andean system, Armenia - Quindío, Colombia (Revista de Investigaciones Universidad del Quindío, 2011)
Some benthic communities were studied in the stream “La Florida” Armenia - Quindío, during a period of five months between February and June, 2009. For that purpose, six points of sampling were established to collect samples of macroinvertebrates and periphytics seaweeds in ephilitc substratum (rock) and epiphytic (vegetable); and samples of water were taken for physic-chemical analysis. To evaluate the ecological structure of the benthic communities, a species accumulation curve was made, and the ecological diversity alpha and beta indices were applied; the alpha index was compared among substratums, places and period of time sampling, using a Kruskall Wallis's test and another test based on averages. The results obtained showed that the macroinvertebrates community registered: 4 classes, 11 orders, 25 families and 32 genera with a total of 12.113 individuals. On the other hand, the periphyton community registered: 4 divisions, 26 families and 42 genera with a total of 23.626 (ind/ml). The macroinvertebrates presented changes in their structure in April, May and June, which are considered traditionally periods of transition, and the rocky substratum was constituted in their favorite habitat; while the periphytics seaweeds did not register changes in their structure in the different months of sampling, in addition, their favorite habitat was the vegetable material. The ecological alpha (á) index showed that the sites 1 and 2 presented a good ecological condition that is used as a shelter for a good number of benthic species, while the sites 4, 5 and 6 presented a habitat and landscape in very bad conditions. It is fundamental to take strategic actions to
Keywords: Macroinvertebrates; Periphyton; Substrates; Ecological index; La Florida stream